Genomic epidemiology reveals transmission patterns and dynamics of SARS-CoV-2 in Aotearoa New Zealand - Jemma L. Geoghegan (Nature Portfolio, 2020)
New Zealand implemented stringent COVID-19 control measures early after identification of its first case. Here, the authors perform whole genome sequencing of samples taken until 22 May 2020 and find high viral diversity indicative of multiple separate introductions and limited community transmission.